Mapping student engagement in health professions education policy and decision-making: a scoping review - Hanieh Neshastesaz Kashi; Salime Goharinezhad; Samira Soleimanpour; Ali Haji Mohammadi (BMC Medical Education, 2024)
Abstract Background “Student engagement” (SE) is gaining momentum as an approach to improve the performance of health professions education (HPE). Nevertheless, despite the broad studies about the role of students in various areas, little is known about the role of SE in policy and decision-making activities. This study aimed to map SE in policy and decision-making regarding terms and definitions, engagement models, influencing factors, outcomes and achievements, and the interconnection between the influencing factors. Method Five databases (PubMed, Scopus, ProQuest, Web of Science, and ERIC) were systematically searched from Jan 1, 1990, to Nov 12, 2022. The review was followed according to the Arksey and O’Malley framework for scoping reviews and reported according to the PRISMA-ScR guidelines. We included articles published in English focusing on HPE policy and decision-making. The authors summarized and synthesized the findings into themes, subthemes, tables, and models. Results Of the 22 articles included in the full-text review, terms and definitions were tabled, and three themes were extracted: 1. models of SE, in which 10 studies (45.5%) presented the highly structured formal models as Organizations, 5 studies (22.7%) reported less-structured community and group as Programs, and 7 studies (31.8%) engaged students only in surveys or interviews as Perspective; 2. Factors influencing SE, that were categorized into 7 subthemes: structural, environmental, and motivational factors, member characteristics, training and mentoring, member relationships, valuing and recognizing. 3. Outcomes and achievements of SE related to systems and members. The interconnection between influencing factors is also demonstrated as a conceptual model. Discussion There are various SE models in HPE policy and decision-making, which are mapped and categorized depending on the degree of formality, structuredness, and level of engagement. In our study, three more common SE models in HPE policy and decision-making were investigated. Additionally, these collaborative methods emphasized curriculum development and quality assurance and employed students in these activities. It is worth mentioning that to make SE models more efficient and sustainable, several influencing factors and their interconnections should be considered.